'We Don't Want to Go and Be Idle Ducks': Family Practices at the End of Life. (December 2019) - Borgstrom, Erica; Ellis, Julie; Woodthorpe, Kate
At present, end-of-life research, policy and practice typically prioritise the dying individual and consider the family an orbiting static unit. Sociological theorising of dying has reflected this trend, focusing on the macro-level and public rather than private sphere, with sociologists engaged in the study of family and relationships overlooking the end of life altogether. In addressing this gap, this article argues that the end of life is a relational experience in which everyday family practices are embedded and enacted. Drawing on two ethnographic studies, it demonstrates some of the ways in which family is actively 'done' at this time, principally in the transference of family practices into institutional settings, and shared decision making. In doing so, it makes a case for moving beyond a highly individualised emphasis on the person nearing the end of their life and an accompanying normative conceptualisation of family, towards an understanding that families (in all their diversity) and their continued (un)making are central to the experience.